Developing a Prosthesis Design using A Gearbox to Replicate the Human Hand Mechanism - Jaber, Haneen Mahdi; -Sattar, Muhammed Abdul; Abd al-Sahib, Nabel Kadhim (Al-Khwarizmi Engineering Journal, 2020)
Prosthetic is an artificial tool that replaces a member of the human frame that is  absent because of ailment, damage, or distortion. The current research activities in Iraq draw interest to the upper limb discipline because of the growth in the number  of amputees. Thus, it becomes necessary to increase researches in this subject to help in reducing the struggling patients.  This paper describes the design and development of a prosthesis for people able and wear them from persons who have amputation in the hands. This design is composed of a hand with five fingers moving by means of a gearbox ism mechanism. The design of this artificial hand has 5 degrees of freedom. This artificial hand works based on the principle of  under actuated system. The used motor is 6V Polulu high-power carbon brush micro metal gearmotor with gear ratio equal to 50:1. The motor was chosen due to its compactness and cheapness. The hand manufacturing process was done using  a 3D printer and using polylactic acid material. Numbers of experiments were accomplished using the designed hand for gripping objects. Initially, the electromyography signal (EMG) was recorded when the muscle contracted in one second, two seconds, three seconds. The synthetic hand was able to produce a range of gestures and grasping for objects.